Efektifitas Pelayanan Publik dalam Memberikan Informasi Pentingnya Memiliki Akta Kelahiran diDukcapil Kabupaten Tangerang - Khasanah, Prisca Dwi Puspa; Mirza, Mochammad; Emelsi, Suci (Social Science Academic, 2024)
Understanding the efficiency of the Dukcapil office in Tangerang Regency regarding the dissemination of information about the significance of obtaining birth certificates for children is crucial. This study adopts a qualitative research approach, specifically employing a case study design. The research framework incorporates the construction paradigm to assess the efficacy of public services provided by the Dukcapil office in Tangerang Regency regarding birth certificate information. The research findings reveal the Soppeng Regency Population and Civil Registration's public services' efficacy Office through the examination of various factors, including service procedures, time reliability, service costs, availability of facilities and infrastructure, employee competencies, and service offerings. Out of the six indicators gauging public service effectiveness, four exhibit positive outcomes. Consequently, it can be inferred that public services at Disdukcapil have been effective, albeit with room for improvement. In summary, the services at Disdukcapil have been conducted efficiently, with suggested enhancements for future refinement.